Steroids and Olfactory Training for Postviral Olfactory Dysfunction: A Systematic Review - Yuan, Fan; Huang, Tianhao; Wei, Yongxiang; Wu, Dawei (Frontiers in Neuroscience, 2021)
Background Postviral olfactory dysfunction (PVOD) is a clinical challenge due to limited therapeutic options and poor prognosis. Both steroids and olfactory training have been proved to be effective for olfactory dysfunction with varied etiologies. We sought to perform a systematic review to summarize the evidence of steroids or olfactory training for patients with PVOD. Methods A systematic literature review using Pubmed, Embase, Cochrane Library, Web of Science was conducted to identify studies assessing olfactory change in patients with PVOD receiving steroid or olfactory training. Results Of the initial 273 abstracts reviewed, 20 articles with data for 2415 patients with PVOD were included. Treatments including topical steroids, systemic steroids, classical olfactory training (COT), modified olfactory training (MOT), and olfactory training with steroid were analyzed. Both psychophysical olfactory testing and subjective symptom scores were utilized to assess the olfactory function. The routine use of nasal steroid spray alone during the management of PVOD seems to have no positive effect on olfactory dysfunction. Direct injection of steroid or nasal steroid spray into the olfactory cleft significantly improved the olfactory function in patients with PVOD. Olfactory improvement is greater than that of the natural course of the disease with short-term COT. Patients with PVOD would benefit more from long-term COT (>12 weeks). Treatment duration, various odorants, olfactory training device, changing the types of odors periodically, different molecular odorants, and different concentrations of odorants tended to increase the efficiency of MOT. Clinically significant improvement after olfactory training was defined as an increase of threshold, discrimination, and identification (TDI) score ≥6. From week 24 to week 36, both COT and MOT groups reached the maximum therapeutic effect regarding the number of participants achieving clinically significant improvement. A combination of local or oral steroids with olfactory training is more efficient than COT only. Conclusion Olfactory function in patients with PVOD was effectively improved through direct steroid administration in the olfactory cleft, COT or modification of COT. The addition of topical steroids to COT therapy showed a tendency of greater olfactory improvement in patients with PVOD.